Effect Of Ease of Use and Trust on Purchase Decisions Through Online Shopping Sites - Suhendar Janamarta Janamarta; Hendra Hendra; Donny Yana (Komunitas Dosen Indonesia, 2021)
This study aims to determine: (1) the effect of ease of use on purchasing decisions through online shopping sites (2) trust in purchasing decisions through online shopping sites (3) the effect of ease of use and trust on purchasing decisions through online shopping sites in the people of Tangerang City. The samples taken were 100 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results of this study indicate that: (1) there is a positive influence of ease of use on purchasing decisions through online shopping sites, as evidenced by the t valuecount of 9,170 a significance value of 0.000 <0.05; and a regression coefficient of 0.687, (2) there is a positive influence of trust on purchasing decisions through online shopping sites, as evidenced by the t valuecount of 3,539 a significance value of 0.001 <0.05; and a regression coefficient of 0.267, (3) there is a positive influence of ease of use and trust on purchasing decisions through online shopping sites, as evidenced by the f valuecount of 131,000 with a significance value of 0.000 <0.05